2021
DOI: 10.2147/dddt.s307015
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Network Pharmacology, Molecular Docking, and Experiment Validation to Explore the New Candidate Active Component and Mechanism of Cuscutae Semen-Mori Fructus Coupled-Herbs in Treating Oligoasthenozoospermia

Abstract: Purpose: One of the most common types of male infertility is recognized as oligoasthenozoospermia (OA), characterized by low sperm count and quality in males. As a traditional Chinese medicine (TCM), Cuscutae Semen-Mori Fructus coupled-herbs (CSMFCH) has been known to act a curative effect on OA for thousands of years. Nevertheless, the substantial basis and molecular mechanism of CSMFCH in treating OA remain elusive. Methods: Herein, an integrated approach, including network pharmacology, molecular docking, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Androgens act via AR, and its signaling in the testis is required for spermatogenesis [59]. The high binding energies of androgen receptor-quercetin or kempferol complexes could be a predictor of the mechanism for improved testicular function and sperm quality, according to the study, which also backed up a previous study that found kaempferol could improve mouse Leydig and Sertoli cell viability, male reproductive organ weights, and sperm quality [60].…”
Section: Discussionmentioning
confidence: 67%
“…Androgens act via AR, and its signaling in the testis is required for spermatogenesis [59]. The high binding energies of androgen receptor-quercetin or kempferol complexes could be a predictor of the mechanism for improved testicular function and sperm quality, according to the study, which also backed up a previous study that found kaempferol could improve mouse Leydig and Sertoli cell viability, male reproductive organ weights, and sperm quality [60].…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, there has been an increasing number of clinical studies on TCM , 76 , 77 , 78 and randomized controlled trials 79 , 80 , 81 have also been carried out one after another, which achieved certain effects and were increasingly recognized by Western Medicine. Therefore, the TCM decoction plays an important role in improving the number of sperm.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the TCM decoction plays an important role in improving the number of sperm. In the fields of network pharmacology, 78 , 82 animal experiments, 81 , 83 , 84 and human experiments, 79 , 80 , 85 , 86 it could be used as a potential development object for cryptorzoospermia.…”
Section: Resultsmentioning
confidence: 99%
“…Bioactive components of UR-AP were identified using the TCMSP (http://tcmspw.com/tcmsp.php) (Ru et al, 2014), TCMID (http://119.3.41.228:8000/tcmid/) (Huang et al, 2018), and DCABM-TCM (http://bionet.ncpsb.org.cn/dcabm-tcm/) (Liu et al, 2023). The ADME model, alongside published literature (Bai et al, 2021a;Bai et al, 2021b;Zhai et al, 2021;Liu et al, 2022), guided the setting of thresholds for oral bioavailability (OB) ≥ 30% and drug-likeness (DL) ≥ 0.18 to screen for bioactive components.…”
Section: Identification Of Bioactive Components In Ur-apmentioning
confidence: 99%